Travelling waves in laser sustained plasma. Constant coefficient case - Kaźmierczak, B. (Archives of Mechanics, 1996)
We use the Conley index theory to prove existence of travelling waves to a system of partial differential equations describing a two-temperature model of plasma sustained by a laser beam. These waves connect two asymptotic state of gas: a cold one and a hot partially ionized one.